Linking Contextual Factors with Rhetorical Pattern Shift: Direct and Indirect Strategies Recommended in English Business Communication Textbooks in China - Wang, Junhua; Zhu, Pinfan (Journal of technical writing and communication, 2011)
Scholars have consistently claimed that rhetorical patterns are culturally bound, and indirectness is a defining characteristic of Chinese writing. Through examining how the rhetorical mechanism of directness and indirectness is presented in 29 English business communication textbooks published in China, we explore how English business communication textbook writers in China keep up with the contextual changes in the Chinese society and how the rhetorical mechanism of directness and indirectness is locally situated in the English business communication teaching practices in China. We conclude that the pedagogical strategy on directness and indirectness represented in Chinese English business communication textbooks echoes the same strategy favored by scholars in the United States.